Sovereignty of A Nation: A Lesson Learnt From the Case of Batu Puteh Island (Pedra Branca) - Azman Suhaimy, Khairul; Jaes, Lutfan; Anuar Kamri, Khairol; Othman, Hussain; Rul Anuar Nordin, Shah; Akmal Damin, Zahrul; Halim, Harliana; Hisyam Abdul Rahim, Mohd; Shakor Borham, Abdul; Fuad Othman, Mohd; Ismail, Marwan; Zain Mubarak, Mohd; et al. (International Journal of Engineering and Technology, 2018)
This paper discusses on the issues related to Batu Puteh Island (Pedra Branca) which is a topic of discussion in relation to the sovereignty of a country and its implications in the future. Losing territories will undermine the sovereignty of a country and is an insult to them. The reality is a bitter truth. Sovereignty is a symbol of power to many countries. The corresponding letter by the Acting Secretary of Johore dated 21st September 1953 stated that Johore does not claim ownership of Pedra Branca. The letter was seen by ICJ as a sign that Johore had handed over its sovereignty on Batu Puteh Island over to the British. Therefore, the court concluded that the letter clearly indicates that since 1953, Johore has declared that it no longer had sovereignty over Pedra Branca. Various questions arise regarding the letter. Where is the authority and sovereign of the Sultan of Johore who ruled over Johore and its territories? Can an Acting Secretary of State legitimately decide on matters of sovereignty, land and territorial rights? Or, should it be decided by the Sultan as head of a sovereign state? These are some of the questions which are yet to be answered and documentation is vital. It will determine the future and the road to success. Learn from history, learn from the administrative weaknesses and individual mistakes, and remember that history repeats itself in the future. Our own mistakes cost us an island which was originally ours for centuries. Our absent mindedness led us in losing the islandâ€™s sovereignty to other nation. Everyone knows that the island belongs to Johore with all related documents are complete and history has proven it. Always be careful when making any decisions or be sorry for life.Â Â